APLIKASI LUBANG RESAPAN BIOPORI BERKOMPOS DI KEBUN KOPI MENINGKATKAN JUMLAH SPORA MIKORIZA ARBUSKULA DAN KOLONI AKAR - Dyah Ayu Prosanti; Budi Prasetya; Soemarno Soemarno (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2023)
Mycorrhizae is a mutualistic symbiotic relationship between fungi and plant roots, and soil characteristics influence the performance of this symbiosis. Biopore Infiltration Hole is a vertical hole into the soil with a diameter of about 10cm and at a depth of ±100 cm in the soil for air infiltration, which is helpful in reducing the occurrence of excessive air puddles. This research was conducted to determine the effect of soil properties such as pH, total N, available P, CEC and texture on the number of spores and root colonies by arbuscular mycorrhizae on the effect of biopore infiltration holes with the addition of organic matter. The results showed that the highest number of arbuscular mycorrhizae spores and root colonies was in the biopore infiltration holes with goat manure, namely 16.3 spores 100 g-1 soil and 66.22% root colonization. The arbuscular mycorrhizal genera found included Glomus, Acaulospora, Scutellospora, and Gigaspora. The number of spores and soil properties that were positively correlated were pH (r=0.45), organic C (r=0.945**), total N (r=0.716**), available P (r=0.922**), dan CEC (r=0.894**).